Penyuluhan terhadap peningkatan pengetahuan dan sikap remaja tentang bahaya narkotika - Adius Kusnan; Amirudin Eso; Asriati Asriati; La Ode Alifariki; Ruslan Ruslan (Holistik Jurnal Kesehatan, 2020)
Educating young people about drugs among high school studentsBackground: Adolescence is a transition between childhood and adulthood. At this stage of development, adolescents have tasks that must be completed, if adolescents are not able to carry out their roles properly they can be involved in the drugs abuse and other addictive substances.Purpose: to analyze the effect of educating young people  on improving the knowledge and attitudes about drugs among high school studentsMethod: A quasi experiment, using a pre-test and post-test design. The population was  all of student council organization such as  of (youth consultation information center, youth red cross, Scouts) and all students in grade XI (high school)  Negeri 4 Kendari. The samples was divided by 2 group: intervention groups (44 respondents) and control groups (44 respondents). Measuring instruments used were pre-test, post-test day 1, and post-test day 2 after intervention. Data analysis used paired t test and unpaired t test.Results: Shows that the briefing regarding of negative of consequence addicted to drugs  had a significant effect on students' knowledge with p-value <α (0,000) and attitude 0,000. Whereas in the control group there was no effect on knowledge (p value = 0.151) and attitudes (p value = 0.141). The results of the independent test t test obtained knowledge of 0,000 while the attitude of 0.082. This shows there is a difference between knowledge in intervention and control groups but there is no difference in attitude between intervention and control groups.Conclusion: There is effectiveness of briefing regarding of negative of consequence addicted to drugs  on knowledge among high school students in Kendari.Keywords: Educating; Young people; Drugs; High school studentsPendahuluan : Masa remaja merupakan masa peralihan antara masa kanak-kanak dan masa dewasa. Pada tahap perkembangan tersebut, remaja memiliki tugas yang harus diselesaikan, bila remaja tidak mampu menjalankan tugas dengan baik mereka dapat terlibat dalam dunia narkotika, psikotropika, obat-obatan terlarang dan zat adiktif lainnya.Tujuan: Menganalisis pengaruh penyuluhan terhadap peningkatan pengetahuan dan sikap remaja tentang bahaya Narkotika  pada remaja pada kalangan siswa SMA Negeri 4 Kendari.Metode: Penelitian quasi experiment, menggunakan rancangan pre test and post test design. Populasinya semua pengurus organisasi siswa siswi terdiri dari (pusat informasi konsultasi remaja/PIKR, palang merah remaja/PMR, Pramuka) dan siswa kelas XI SMA Negeri 4 Kendari. Sampel dibagi dalam 2 kelompok meliputi kelompok perlakuan (44 responden) dan kelompok kontrol (44 responden). Alat ukur yang digunakan kuesioner pre test, post test hari ke-1, dan post test hari ke-2 setelah penyuluhan. Analisis data menggunakan uji T berpasangan dan uji T tidak berpasangan.Hasil: Pada kelompok perlakuan (penyuluhan) menunjukkan bahwa pemberian penyuluhan tentang narkotika berpengaruh signifikan pada pengetahuan siswa yakni p value < α (0,000) dan sikap 0,000. Sedangkan pada kelompok kontrol tidak ada pengaruh penyuluhan terhadap pengetahuan (p value = 0,151) dan sikap siswa (p value = 0,141). Hasil uji indenpenden T test diperoleh pengetahuan sebesar 0,000 sedangkan pada sikap 0,082. Hal ini menunjukkan ada perbedaan antara pengetahuan pada kelompok perlakuan dan kontrol akan tetapi tidak ada perbedaan sikap antara kelompok perlakuan dan kontrol.Simpulan: Kesimpulan bahwa ada pengaruh penyuluhan terhadap peningkatan pengetahuan remaja tentang bahaya narkotika di Sekolah Menenganh Atas Negeri 4 Kendari.